Commitment in the process of translation and control of strategy in Brazilian agro-industrial cooperatives - Ferreira Barreiros, Reginaldo; Max Protil, Roberto; Carlos Duclós, Luiz; Rodrigues Moreira, Vilmar (REBRAE, 2016)
This paper deals with the insertion of commitment as a critical success factor in a model of strategy’s translation and control in agro-industrial cooperatives in the context of the Brazilian reality, and more specifically of an agro-industrial cooperative, located in the State of Parana. Based on the theoretical background of strategy’s translation and control and on agro-industrial cooperatives, interviews were conducted with experts on cooperatives, followed by thematic content analysis, cooccurrences and structural analysis. Subsequently an instrumental case study in an agro-industrial cooperative was performed, also by means of interviews with managers, followed by thematic content analysis, co-occurrences and structural analysis. The paper discusses several interactions that commitment has with other factors of the strategy’s translation and control model in agroindustrial cooperatives. It follows that such model must consider the commitment, as a critical success factor, related to the control lever of the cooperative positioning. Commitment leads to the establishment of incentives for cooperation by the cooperative; and the emergence, strengthening and consolidating of member’s fidelity; fundamental conditions for the sustainability of the cooperative system. It also concludes that fidelity is positively influenced by the organizational culture of the cooperative; by the satisfaction of members - derived from the economic performance of their farms -; and also by the integration and control exercised by the technical assistance. This conclusion, regarding the cultural question, refers to the theoretical concept of commitment as the member’s preference associated with something that is offered, in a different way, by the cooperative, in relation to investor owned firms, and which had its beginning in the cooperative doctrine.